PENGARUH NPL DAN BOPO TERHADAP PROFITABILITAS PADA BANK UMUM KONVENSIONAL PADA MASA PANDEMI COVID 19 - Lorenzia Ida Ayu Irma Hartiwi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to determine the effect of Non-Performing Loans (NPL) and Operational Costs and Operating Income (BOPO) on Profitability carried out at Conventional Commercial Banks during the 2020 Covid-19 pandemic. This study uses secondary data obtained from financial reports and data other financials for the 2020 Quarterly period taken via the web www.ojk.go.id. The sample in this study is Financial Reports for Quarters I to IV of 2020 at conventional commercial banks with a total of 149 samples. The results showed that NPL had a significant negative effect on ROA profitability and BOPO had no significant effect on ROA profitability.